TOKSISITAS EKSTRAK DAUN JERUK NIPIS (Citrus aurantifolia L) DAN EKSTRAK SERAI (Cymbopogon nardus L) PADA LARVA NYAMUK Aedes aegypti - S.Z Nisak; Susie Amilah (FMIPA : Universitas PGRI Adi Buana, 2014)
ABSTRACT This study aims to menegetahui effect of leaf extracts of lime (Citrus aurantifolia) and extract lemongr ass (Cymbopogon nardus) on mortality of larvae of Aedes aegypti and A. aegypti. The design of this study used a sample of 500 larvae of A. aegypti who has reached the third instar, the test was divided into 2 groups, each group has the same concentration of test ie 0, 0,5, 1,0, 1.5, and 2,0 g / l. Each test group contained 25 larvae in the leaf extract solution of lime and lemongrass with replication performed 4 times. Based on the analysis of the effect of the leaf extract of citrus and lemon grass extracts and concentrations that meet the criteria in the ability to kill larvae were started at a concentration of 0, 0,5, 1,0, 1,5, and 2,0 g/l. Concentration of extract lime leaves and lemongrass extracts can kill mosquito larvae A. aegypti is the lime leaf extract concentration of 2,0 g / l with an average mortality of larvae as larvae 18,75. While the lemongrass extract concentrations that kill larvae more effectively is 2,0 g / l with an average mortality of larvae as larvae 16,25. T-test results showed that there was no significant difference (P> 0,05) between the leaf extract lemon with lemon grass extract against mosquito larvae mortality rate A. aegypti. Can be concluded that the leaf extract of lemon and lemongrass naymuk effect on mortality of larvae of A. aegypti. Lethal concentration 50 to extract lime leaves and lemongrass extracts respectively 1,57 and 1,59 g / l in water. Keywords: lime, lemon grass, A. aegypti, and mortality